A graphical approach for mixed ratio optimisation in the binary mixed amine solution. (1st June 2022) - Wang, Yi; Guo, Lianghui; Wang, Bohong; Klemeš, Jiří Jaromír
Abstract: Chemical absorption method plays an important role in the process of CO2 separation. One major problem for chemical absorption is huge energy consumption, which is affected by the performance of absorbents. Developing a type of absorbent with high absorption capacity and low regenerative energy consumption is a research topic that attracts attention. The combination of two or more amines is one way to develop new solvents. However, the change of amine liquid ratio can cause a series of complex nonlinear changes in absorption capacity, absorption heat, the heat of vaporisation and sensible heat. It is of interest to visualise the amine solution mixing ratio optimisation to help reduce the energy consumption and increase the absorption capacity. Derivative analysis of standardised vs variables diagram (DSVD), a kind of graphical method based on maximum benefit and minimum consumption, is proposed to determine the optimal mixing ratio of binary amine solution. This novel approach helps to visualise what kind of amines are not suitable for compounding, what kind of amines have the best compounding ratio, and how to determine the optimal compounding ratio. The optimal mixing ratio of the Methyldiethanolamine (MDEA) - Piperazine (PZ) system and MDEA - Monoethanolamine (MEA) were optimised by this method. The optimal ratio of MDEA - PZ and MDEA - MEA are 0.6 (PZ: MDEA = 0.6:0.4, wt.%) and 0.8 (MEA: MDEA = 0.8:0.2, wt.%). Highlights: Derivative analysis of standardised vs variables diagram (DSVD) is proposed. A new method to determine the optimal mixing ratio of binary amine solution. Multi-objective graphic solution based on benefit and consumption. The mixing ratio of MDEA + MEA system and MDEA + PZ system was optimised.